Urgensi Pelayanan Kesehatan Masyarakat dalam Misi Gereja: Analisis Pelayanan Kesehatan Klinik Air Hidup Yayasan Mahanaim di Bekasi, Jawa Barat - Lia Sitompul; Fendy Ongko; Eunike Eunike; Simon Simare (Sekolah Tinggi Teologia Kerusso Indonesia, 2025)
This study aims to analyze the urgency of community health services as part of the church's mission through a case study of the Health Service at Klinik Air Hidup Yayasan Mahanaim in Bekasi, West Java. The research focuses on the role of health services within the framework of the church's mission and its relevance to the health needs of the urban community. This study uses a qualitative method. Data collection was carried out through in-depth interviews with the clinic's management and staff, observations of health service delivery, and document reviews related to the foundation's vision, mission, and service programs. Data were analyzed descriptively-analytically with reference to the perspective of mission theology and church social services. The findings show that the health services provided by Klinik Air Hidup serve as a form of holistic church mission, which is not only focused on medical aspects but also on social and humanitarian dimensions. These services contribute to improving access to healthcare for the surrounding community and strengthening the church's presence in a contextual manner. This finding emphasizes that community health services have a strategic urgency in the implementation of the church's mission, particularly in addressing the challenges and needs of urban communities.